(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This paper examines the significance of biologically active supplements (BAS) in maintaining and improving human health. Particular emphasis is placed on their clinical effectiveness, safety profile, and evidence-based use as reported in contemporary scientific literature.